Investigation of the diffusion of the ultrasonicated antiseptic aqueous solution of nanosilver in the tooth's dentin (LLC "Endo Press", 2020)
The depth of penetration of the bactericidal aqueous solution of nanosilver Poviargrol into Dentinal Tubules of the tooth was studied. It is shown that the introduction of the solution with phonophoresis provides a greater degree of diffusion of nanosilver into the dentin in comparison with free penetration.